Early education for all: is there a role for the private sector? - Woodhead, M; Streuli, N (Oxford University Press, 2013)
The “private-for-profit” sector is a significant provider of global early childhood care and education (ECCE). This chapter explores how this trend contributes to policy goals, focusing especially on the risks that a growing private-for-profit sector may amplify inequities in access and quality. We review the government financing and regulation required to harness private sector providers to achieve comprehensive ECCE goals, recognizing that the private sector varies in respect to finance, management, and client group. We offer a taxonomy of four major functions for the private-for-profit sector in its relationship to public policies and services, drawing on case studies in Peru, Ethiopia, and India. The potential of public-private partnerships (PPPs) has been widely discussed in relation to early childhood, but less commonly implemented fully. We also discuss the risks of current laissez-faire approaches, favoring positive, pro-equity policies, including adequate governance of the private sector, which is not an alternative to quality publicly funded services.